Enterprise Architecture as a Smart Village Development Strategy with a Focus on Economic Services Using TOGAF 9.2 (Case Study: Advanced Village in Jambi Region) - Jannah, Putri Raudatul; Fajrillah, Asti Amalia Nur; Nurtrisha, Widyatasya Agustika (Universitas Negeri Padang, 2024)
The smart village is the digital transformation concepts used to organize the economic sector improvement within the village government's scope in supporting and realizing the SDG's sustainable development goals. The selection of objects in this study was based on the Developed Village Index (IDM) classification in the Advanced Village group. Desa Sembubuk is one of the villages in Jambi Province with the status of IDM Advanced Village. The Sembubuk Village Government can carry out smart village implementation to optimize and increase the effectiveness and efficiency of village economic improvement programs such as community skills training and BUMDes management. In implementing a smart village, there must be alignment between the government's strategic plans and technological needs. For this reason, Enterprise Architecture (EA) design is required. The guidelines for creating EA in this study use the TOGAF 9.2 framework. The result of this research is an IT Roadmap and EA design in Sembubuk Village, which can be used as a guide in implementing a smart village.